Analisis Pengujian Pengaduan Konstitusional (Constitutional Complaint) pada Mahkamah Kostitusi Indonesia sebagai Salah Satu Upaya Perlindungan Hak-Hak Warga Negara - Rifandy Ritonga (KEADILAN PROGRESIF, 2016)
Constitutional rights are the rights guaranteed by the Constitution, the Constitution is the fundamental law (fundamental) the constitutional rights as fundamental rights which must be protected. But in this case at the Constitutional Court of Indonesia do not have the means of constitutional complaint (Constitutional Complaint) as an extraordinary legal remedy in defending the constitutional rights of every individual citizen. Constitutional Complaint is a complaint or a lawsuit filed by an individual (citizen) to the court, in this case the Constitutional Court, to an act or omission committed by an institution or public authority that resulted in the violation of the fundamental rights of citizens. Urgency authority to hear Constitutional Complaint in the Constitutional Court of the Republic of Indonesia as an effort to protect the rights of citizens is needed. The granting of the authority to hear Constitutional Complaint in the Constitutional Court of Indonesia was to ensure that there are no loopholes in the law enforcement efforts to protect the constitutional rights of citizens.